A Type of MOF-Derived Porous Carbon with Low Cost as an Efficient Catalyst for Phenol Hydroxylation - Renjie Zhou; Gui Chen; Yuejun Ouyang; Hairui Ni; Nonglin Zhou; Bailin Xiang (Journal of Chemistry)
Using MOF-5 as a template, the porous carbon (MDPC-600) possessing high specific surface area was obtained after carbonization and acid washing. After MDPC-600 was loaded with Cu ions, the catalyst Cu/MDPC-600 was acquired by heat treatment under nitrogen atmosphere. The catalyst was characterized by X-ray powder diffraction (XRD), N2 physical adsorption (BET), field emission electron microscope (SEM), energy spectrum, and transmission electron microscope (TEM). The results show that the Cu/MDPC-600 catalyst prepared by using MOF-5 as the template has a very high specific surface area, and Cu is uniformly supported on the carrier. The catalytic hydrogen peroxide oxidation reaction of phenol hydroxylation was investigated and exhibits better catalytic activity and stability in the phenol hydroxylation reaction. The catalytic effect was best when the reaction temperature was 80°C, the reaction time was 2 h, and the amount of catalyst was 0.05 g. The conversion rate of phenol was 47.6%; the yield and selectivity of catechol were 37.8% and 79.4%, respectively. The activity of the catalyst changes little after three cycles of use.